A SEM Analysis Of Visitors' Interest In Pari City Village Tourism, Pantai Cermin District, Serdang Bedagai Region - Ritonga, Husni Muharram; Indrawan, Muhammad Isa; Sari, Dian Septiana (Journal of Community Research and Service, 2022)
Pari City is one of the villages in the Serdang Bedagai District of Pantai Cermin. A narrative relating to the village's location, which is surrounded by beaches, revealed the village's name as Pari, according to information from locals. On one of these beaches, stingrays are rumored to congregate. There are a significant number of stingrays on the shore, making their capture easy for everyone. Over time, word of the quantity of stingrays in this village spread to neighboring communities, luring many people from other villages to come and catch them. People from surrounding villages are unaware of this village's former name, and the people do not have a moniker for their community. Due to the abundance of stingrays along this community's coastline, people from outside the village have dubbed it the City of Pari. The explanation is obvious since, according to the legend, the profusion of stingrays resembles a city because there are so many of them, and over time people have grown accustomed to calling it the City of Stingrays. According to tales told by locals, stingrays were formerly abundant on the beach, but they are now extremely rare and almost never seen again due to commercial fishing and trading. Therefore, Kota Pari Village is deemed essential for usage as a tourist destination, and tourism development and development in this village are anticipated to optimize the potential and principal functions and give additional value to raise Village Original Income (PADes) and Regional Original Income (PAD). Moreover, it is anticipated that tourism will enhance the level of community welfare, particularly for the local village community and generally for the inhabitants of Kota Pari Village. Using the Structural Equation Modeling (SEM) technique, the correlation between each indicator and variable is analyzed to determine the level of interest in a visit. It is intended that the SEM method study will provide input and strategic plans for the growth and expansion of Kota Pari Village Tourism